2011
DOI: 10.1136/bmjopen-2011-000142
|View full text |Cite
|
Sign up to set email alerts
|

Are physiological attributes of jockeys predictors of falls? A pilot study

Abstract: ObjectivesThis pilot study describes the physiological attributes of jockeys and track-work riders in Tasmania and investigates whether these attributes are associated with falls.MethodsAll jockeys and track-work riders licensed in Tasmania were invited to participate. The study group consisted of eight jockeys (two female, six male) and 20 track-work riders (14 female, six male). Measures of anthropometry, balance, reaction time, isometric strength, vertical jump, glycolytic and aerobic fitness, flexibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Additional information—such as previous skills and knowledge obtained while working with horses prior to commencing their apprenticeship, experience gained through track-work riding and barrier trial rides, and on career history including sanctions for careless riding—would have strengthened this study. Further, as noted previously,10 information was not available on physiological attributes of the jockeys—such as aerobic and anaerobic fitness—which, in our pilot study of jockeys and track-work riders,13 were found to be potentially important predictors of falls. Furthermore, extraneous factors such as the size of the crowd at the race meeting could also be important confounders or effect modifiers, especially where the jockey is less experienced and/or the horse is less accomplished.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additional information—such as previous skills and knowledge obtained while working with horses prior to commencing their apprenticeship, experience gained through track-work riding and barrier trial rides, and on career history including sanctions for careless riding—would have strengthened this study. Further, as noted previously,10 information was not available on physiological attributes of the jockeys—such as aerobic and anaerobic fitness—which, in our pilot study of jockeys and track-work riders,13 were found to be potentially important predictors of falls. Furthermore, extraneous factors such as the size of the crowd at the race meeting could also be important confounders or effect modifiers, especially where the jockey is less experienced and/or the horse is less accomplished.…”
Section: Discussionmentioning
confidence: 78%
“…Most importantly, indicators of lesser accomplished horses were found to modify (by increasing) the hazard of falls for lesser experienced jockeys, further highlighting the need to investigate specific skills that experienced riders use when riding inexperienced horses as we have previously noted10 and the need for a thorough study of the physiological attributes—including fitness, strength and riding style—of successful riders 13. Several Principal Racing Authorities of Australia already have policies or local rules in place that restrict apprentice jockeys from riding 2-year-old or unraced horses until the apprentice has ridden in a prescribed number of official races or barrier trials or has otherwise satisfied the stipendiary stewards.…”
Section: Discussionmentioning
confidence: 85%
“…Lack of conditioning may not only be an obstacle to a jockey's progression in the industry but an important factor in their risk of falling from the horse and thus potentially sustaining career ending injuries [4,28,29]. This observational study provides an initial external workload from which further research is required to understand the current level of training (internal and external workloads) undertaken by apprentices and jockeys and to determine whether it is sufficient to meet the demands of the sport.…”
Section: High Workload Cohort Jockeysmentioning
confidence: 99%
“…the New Zealand Polo Association) and reviewed annually; therefore, it could not be manipulated by the researchers. The dependent variables of interest were selected as strength assessments related to horse riding skill or body position (hand grip; isometric mid-thigh pull (IMTP)) and mimicked the dynamic requirements of Polo (reaction time) [8,9].…”
Section: Experimental Approachmentioning
confidence: 99%
“…Horse riding requires physical strength through both the upper and lower limbs, general cardiovascular endurance, balance, reaction time and flexibility [8,9], with these elements further complicated by the grips, sudden accelerations / decelerations, and reaction times required when the dynamic and unpredictable demands of Polo gameplay are introduced. The need to identify, train, and evaluate the physical attributes required for effective and safe Polo performance is crucial [10], as players may be exposed to speeds exceeding 60km/h and distances upwards of 5km per chukka [1,11] which potentiates a variety of risks and potential for injury [1].…”
Section: Introductionmentioning
confidence: 99%